O-010 Novel Regulation of Autophagy and Intestinal Homeostasis Via mRNA Binding Protein IMP1. (March 2016) - Hamilton, Kathryn; Chatterji, Priya; Andres, Sarah; Lundsmith, Emma; Whelan, Kelly; Mizuno, Rei; Giroux, Veronique; Mah, Amanda; Chua, Lillian; Hicks, Philip; Van Landeghem, Laurianne; Lund, P.; et al.
Abstract : Background: IMP1 (Insulin-like growth factor-2 mRNA binding protein 1) is essential for normal gut development and aberrant overexpression promotes colorectal tumors; however, the role of IMP1 in epithelial homeostasis in the adult intestine remains unclear. Our preliminary findings suggest that Imp1 loss may alter autophagy in intestinal epithelium during homeostasis and response to injury. Recent studies have linked aberrations in autophagy to Crohn's disease. We therefore sought to determine if Imp1-mediated changes in autophagy may affect response to injury in the intestine epithelium and whether Imp1 expression is altered in Crohn's disease patients. Methods: Mice with intestine-epithelial specific Imp1 deletion ( VillinCre;Imp1 fl/fl ) were used to evaluate autophagy flux and response to irradiation or Heligmosomoides polygyrus infection via gene expression analyses, flow cytometry, and IHC/IF. Crypt enteroid assays were utilized to evaluate stem cell growth. Imp1 expression in Crohn's disease patients was evaluated via qRT-PCR. Results: Imp1 expression is enriched in the crypt region of the small intestine, and VillinCre;Imp1 fl/fl mice exhibit an increase in autophagy flux and enhanced expression of Paneth and stem cell markers in isolated crypts. Following challenge with irradiation or Heligmosomoides polygyrus infection, VillinCre;Imp1 fl/fl mice exhibit robust crypt enteroid growth and improved clinical parameters consistent with Imp1 loss being protective in these contexts. Analysis of tissue biopsies from Crohn's disease patients reveal a significant upregulation of Imp1 compared to unaffected patients, suggesting the possibility that overexpression of Imp1 may contribute to autophagy-related pathogenesis in Crohn's disease. Conclusions: Our data demonstrate in 2 independent models that intestinal epithelial deletion of Imp1 promotes enhanced recovery from injury, possibly due to upregulation of stem cell gene expression and autophagy. Furthermore, our data reveal for the first time that Imp1 expression is increased in tissue from Crohn's disease patients. Taken together, our findings may suggest a novel mechanism for IMP1 to promote pathogenesis of Crohn's disease via negative regulation of autophagy.